Peningkatan Kualitas Pembelajaran Matematika Melalui Penerapan Metode Tutor Sebaya Pada Murid Kelas Iv Sdn Topa Baubau - Irsan Irsan (JKPD (Jurnal Kajian Pendidikan Dasar), 2018)
Improving the Quality of Mathematics Learning through the Application of Peer Tutor Method on Student IV of SDN Topa Baubau. Irsan. Primary teacher education. Faculty of Teacher Training and Education. University of Muhammadiyah Buton.This research is a classroom action research that aims to improve the quality of Mathematics learning through the application of Peer Tutor method to fourth grade students of SDN Topa Baubau in the even semester of academic year 2017/2018 with a total of 30 students. This research was conducted in two cycles. Each cycle has several stages: planning, execution, observation / observation, and reflection. Each cycle is held in 4 meetings. Data retrieval is done by using learning result test and observation. The collected learning result data was analyzed by using quantitative analysis and observation data was analyzed qualitatively. The results showed that the average score of students in the first cycle was 60.66, while in cycle II obtained an average score of 78. KKM standard used in schools is 65, it indicates that has been achieved student learning outcomes in class. From the results of this study can be concluded that by applying the Tutor Sebaya method of learning quality of Mathematics in fourth grade students of SDN Topa Baubau can increase. Keywords: Peer Tutor Method. Quality of Mathematics Learning. Peningkatan Kualitas Pembelajaran Matematika melalui Penerapan Metode Tutor Sebaya pada Murid Kelas IV SDN Topa Baubau. Irsan. Pendidikan Guru Sekolah Dasar. Fakultas Keguruan dan Ilmu Pendidikan. Universitas Muhammadiyah Buton. Penelitian ini adalah penelitian tindakan kelas  (classroom action research) yang bertujuan untuk meningkatkan kualitas pembelajaran Matematika melalui penerapan metode Tutor Sebaya pada murid kelas IV SDN Topa Baubau semester genap tahun ajaran 2017/2018 dengan jumlah murid 30 orang. Penelitian ini dilaksanakan sebanyak dua siklus. Tiap siklus memiliki beberapa tahapan yaitu perencanaaan, pelaksanaan, pengamatan/observasi, dan refleksi. Masing-masing di siklus dilaksanakan 4 kali pertemuan. Pengambilan data dilakukan dengan menggunakan tes hasil belajar dan observasi. Data hasil belajar yang terkumpul dianalisis dengan menggunakan analisis kuantitatif dan data hasil observasi dianalisis secara kualitatif. Hasil penelitian menunjukkan bahwa skor rata-rata murid pada siklus I adalah 60,66, sedangkan pada siklus II diperoleh skor rata-rata  78. Standar KKM yang digunakan di sekolah adalah 65, hal ini menunjukkan bahwa telah tercapai hasil belajar murid secara klasikal. Dari hasil penelitian ini dapat disimpulkan bahwa dengan menerapkan metode Tutor Sebaya kualitas pembelajaran Matematika pada murid kelas IV SDN Topa Baubau dapat meningkat. Kata kunci: Metode Tutor Sebaya. Kualitas Pembelajaran Matematika.